Welfare Management that Affects Motivation of a Government Agency - สอาดเอี่ยม, จุฑามาศ; พฤกษอาภรณ์, สุวิตา; รอดแจ่ม, ชุมพล; นิลอรุณ, พนิดา (Journal of Humanities and Social Sciences, Rajapruk University, 2019)
The objectives of this research were to study 1) guidelines for the welfare of employees in government agencies, 2) the opinions of employees in the government agencies on the welfare arrangements, and 3) guidelines for the welfare arrangements that affect the labor force. Motivation for employee performance the researcher chose the research area which is an area within a government organization, collecting data from 30 plan and project division staff. The instrument used in this research was a semi-structured interview form. The results of the research revealed that welfare guidelines can be divided into 4 forms which are (1) self-welfare (2) family welfare (3) capital welfare and (4) flexible welfare. Regarding the opinions of employees in government agencies towards the welfare provided by the employees, it is an attraction to employees' intentions. Very committed to the operation and ways of providing welfare that motivate employees to work more efficiently must come from understanding the true needs of employees.